Efficient All‐Inorganic Sb2S3 Solar Cells with Matched Energy Levels Using Sb2Se3 as Hole Transport Layers. Issue 4 (6th January 2022) - Deng, Hui; Chen, Siwei; Ishaq, Muhammad; Cheng, Yingshun; Sun, Quanzhen; Lin, Xiao; Zheng, Qiao; Zhang, Caixia; Cheng, Shuying
Abstract : Sb2 S3 has emerged as a promising light‐absorbing material due to its nontoxicity, low cost, high stability, and absorption coefficient. However, the absorption spectrum ranges and back‐contact barrier between Sb2 S3 and Au strongly limit the device performance. p‐type Sb2 Se3 has a similar lattice structure and properties as Sb2 S3, obtaining absorption expansion and ohmic back contact. Herein, efficient all‐inorganic planar Sb2 S3 solar cells with the addition of Sb2 Se3 layers are fabricated. The functions of Sb2 Se3 as cooperative absorber (400 nm) and hole transport layers (HTL, 80 nm) are further explored. Systematic characterizations indicate that the junction quality and depletion widths of the device with the addition of Sb2 Se3 are improved by forming a p–i–n structure. As a result, the all‐inorganic Sb2 S3 solar cell with a Sb2 Se3 HTL greatly increases the power conversion efficiency from 2.7% to 5.8% and the fill factor from 40% to 55.4%. The additional Sb2 Se3 /Au interface with matched energy‐level alignments reduces the back‐contact barrier and facilitates hole transport and collection. The present design and methods promote the development of Sb2 S3 solar cells. Abstract : All‐inorganic Sb2 S3 thin‐film solar cells with Sb2 Se3 functions as cooperative absorbers and hole transport layers (HTL) are designed to overcome the absorption limit and back‐contact barrier. The device with a Sb2 Se3 HTL greatly increases the efficiency from 2.8% to 5.8% and the fill factor from 41% to 55%. The matched energy‐level alignments reduce the contact barrier and suppress the interface recombination.